2010
DOI: 10.3171/2010.8.gks10994
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of radiosurgical results in patients with brain metastases according to the number of brain lesions: is stereotactic radiosurgery effective for multiple brain metastases?

Abstract: Object Whole-brain radiation therapy (WBRT), open resection, and stereotactic radiosurgery (SRS) are widely used for treatment of metastatic brain lesions, and many physicians recommend WBRT for multiple brain metastases. However, WBRT can be performed only once per patient, with rare exceptions. Some patients may require SRS for multiple metastatic brain lesions, particularly those patients harboring more than 10 lesions. In this paper, treatment results of SRS for brain metastasis were analyzed, and an attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 29 publications
2
76
2
4
Order By: Relevance
“…Together, these studies support our findings that KPS score, as opposed to the number of metastases, is more significantly associated with OS in patients undergoing SRS. Our finding of a trend towards worse intracranial diseasefree survival is consistent with an analysis of 323 patients with 1 to 5, 6 to 10, 11 to 15, and 16 to 20 brain metastases by Chang et al 18 Like ours, this study did not demonstrate differences in OS based on number of brain metastases. However, the patients with Z16 metastases in this study had a greater risk of intracranial recurrence (P = 0.014) and remote disease progression (P = 0.014).…”
Section: Discussionsupporting
confidence: 94%
“…Together, these studies support our findings that KPS score, as opposed to the number of metastases, is more significantly associated with OS in patients undergoing SRS. Our finding of a trend towards worse intracranial diseasefree survival is consistent with an analysis of 323 patients with 1 to 5, 6 to 10, 11 to 15, and 16 to 20 brain metastases by Chang et al 18 Like ours, this study did not demonstrate differences in OS based on number of brain metastases. However, the patients with Z16 metastases in this study had a greater risk of intracranial recurrence (P = 0.014) and remote disease progression (P = 0.014).…”
Section: Discussionsupporting
confidence: 94%
“…Beyond achieving accuracy in the detection of metastatic lesions, as was done in the previous work, determining the exact number of metastatic lesions present on a given scan, as was done in our study, is critical because radiotherapy treatments are now being used for patients with more than 4 metastatic foci. 3,28 The present study is not without limitations. As noted in previous works, histologic confirmation of metastatic lesions is difficult because metastatic lesions are not typically resected in patients with multiple lesions.…”
Section: Figurementioning
confidence: 90%
“…1,2 However, patients with greater numbers of lesions are now routinely treated with stereotactic radiotherapy. 3 Because local control of metastases is more efficacious when lesion size is less than 10 mm in diameter, accurate detection of small brain metastases is critical.…”
mentioning
confidence: 99%
“…36 Such a swing in the pendulum is supported by a growing body of retrospective data indicating that SRS is not only feasible but effective in treating even 20 or more brain metastases. 37,38 For instance, in a recent retrospective study analyzing the outcome of treating multiple brain metastases with SRS alone in 323 patients (mean age 59 years, KPS score P 70), of which 108 patients harboured more than five lesions and 33 more than 15, 38 the authors reported not only an overall favourable median survival of 10 months but more importantly the survival rate and local tumour control rate did not appear to depend on tumour multiplicity. These results, although limited by their retrospective nature, suggest that high tumour multiplicity alone should not be considered a contraindication for SRS.…”
Section: Surgery Compared To Radiosurgerymentioning
confidence: 94%